(untitled) (Research, Society and Development, 2025)
Infective Endocarditis (IE) remains a serious public health problem due to its high morbidity and mortality. Its clinical management is usually dependent on observational studies because of the scarcity of wellconducted randomized clinical trials. Aim: Highlight the aspects of pathophysiology, diagnosis, prevention and new updates on treatment and therapies that change the course of the disease, as well as identify gaps that require additional research. Methodology: Narrative review composed of articles published in the last 20 years (41 studies were found), as well as the 2023 European Cardiology Guideline and the 2020 Update of the Brazilian Guidelines for Valvular Heart Disease. Results: The diagnosis is increasingly refined through the Modified Duke Criteria, modernization of new microbiological and imaging methods. As for complications, the most prevalent and with epidemiological importance are highlighted. The treatment involves the eradication of infection with the use of antibiotics and surgery may be necessary in some cases, especially if there are complications. It is important that patients with a history of IE or specific heart conditions are closely monitored and receive appropriate guidance about preventive care. Conclusion: IE continues to be challenging and riveting, with the need for a multidisciplinary approach. More robust studies with good evidence are essential, resulting in more assertive approach.